ANALISIS DETERMINAN EFEKTIVITAS ORGANISASI KECAMATAN KRAMAT JATI - Muhammad Farrel Ronan; R Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2022)
District has an important role because it brings public services closer to the community. However, in its operation, district often faces complex problems, especially managerial problems. This study aims to examine the relationship between leadership and organizational effectiveness, motivation and organizational effectiveness, and leadership and motivation with organizational effectiveness. This study uses correlational quantitative methods, with interview, questionnaire, observation, and documentary data collection techniques with primary and secondary data sources. The results of this study indicate that Leadership (X1) has a positive and significant relationship to Organizational Effectiveness (Y) in Kramat Jati District. So the better the leadership, the better the effectiveness of the organization. Motivation (X2) also has a positive and significant relationship/correlation to Organizational Effectiveness (Y) in Kramat Jati District. So the better the motivation, the better the effectiveness of the organization. Simultaneously Leadership (X1) and Motivation (X2) have a significant relationship to Organizational Effectiveness (Y). So that if leadership and motivation are improved, it will also increase the effectiveness of the organization. Recommendations that can be given are Kramat Jati District can apply the staff of the month, Kramat Jati District leaders must be able to utilize available resources, and Kramat Jati District employees need to receive training on new skills to improve organizational effectiveness, leadership, and variables. motivation.